USAHA PENGGEMUKAN SAPI POTONG BERBASIS LIMBAH INDUSTRI KELAPA SAWIT (KASUS PADA KELOMPOK TERNAK DI DESA BUKIT HARAPAN KECAMATAN KERINCI KANAN KABUPATEN SIAK) - Sigit Budi Setiawan; Septina Elida (UIR Press, 2014)
Fattening beef cattle waste based palm oil industry began to interest the public because it provides considerable advantages in addition to the low feed costs. This study aims to analyze the allocation of the use of factors of production, costs, production, revenue and efficiency of fattening beef cattle based on the palm oil industry waste herd . This study uses a survey conducted in the Bukit Harapan village Kerinci Kanan Subdistrict, Siak district, from November 2011 to February 2012. Samples taken in the census of livestock group Maju Bersama, Soneta and Mandiri. The analysis showed that the Maju Bersama maintain herd of cows 71 tail, feed 2,696 tons/period and labor 3 people with the cost of production per period amounted to Rp 692,116,347 and net income of Rp 427,979,653. Cost of In Soneta maintains a herd of cows 63 tail, feed 2,391 tons /period and labor 3 people at a cost of Rp 597,659,673 production and net income of USD 321 258 327 with RCR is 1.54. While maintaining herd Mandiri 40 head of cows, feed 1,519 tons/period and labor 2 production cost of Rp 412,668,000 and net income of Rp 244,772,000 with RCR was 1.59.